Ecological aspects of use of biological preservatives «Вioplant» in silage grasses and legumes - Hodarenok, Elena P.; Kurepin, Alexander A. (Journal of the Belarusian State University. Ecology, 2019)
Procurement of silo forage from cereal and leguminous herbs using Bioplant a biological preservative on the basis of lyophilized dried strains of Lactobacillus acidophilus, Lactobacillus plantarum, Lactobacillus casei allowed to get a feed with a nutritional value of 9,78 MJ of metabolizable energy per 1 kg of dry matter; and reduce the loss of dry matter by 5,9 %, of crude protein by 7,7 %, to increase milk productivity of cows by 5,6 %. «Bioplant» рreservative of domestic production is ecologically clean, does not have irritating and allergic effect. In the course of its application, there is no negative effect on the environment and the animal’s organism.